Labor Market Structure in Indonesia: Segregation or Integration of Occupations? - Yunisvita Yunisvita; Muhammad Teguh; Rosmiyati Chodijah; Imelda Imelda; Arika Kurniawan (Muhammadiyah University Press, 2021)
This research discusses occupational segregation of workers based on gender in 2015 - 2018 in Indonesia. This study also aims to measure the level of dissimilarity or how much segregation occurs in the labor market in Indonesia. The sample data used were both males and females labor includes residents aged 15 years and over, namely workers aged 35-44 years. Measurement of occupational segregation is based on between occupational groups and provinces which is explained by a dissimilarity index. A dissimilarity index was constructed to measure occupational segregation. First, the percentage of all workers in each province where each occupation group is calculated. This index is then half the absolute value of the difference between the specific locations of the distribution. The occupational structure in Indonesia during the observed period shows that there is no occupational segregation based on gender where the index number D tends to be closer to zero. The occupation of the leadership and management of men and women workers is the most integrated. From the index number D, it means that female workers are less segregated in all types of occupation in the labor market in Indonesia. Integration is showing signs of increasing in Professional occupations, technicians and the like; Administration; Sales Business; and agricultural, forestry, hunting and fishery businesses.